Pathogenesis of varroosis at the level of the honey bee (Apis mellifera) colony. (August 2016) - Wegener, J.; Ruhnke, H.; Scheller, K.; Mispagel, S.; Knollmann, U.; Kamp, G.; Bienefeld, K.
Graphical abstract: Highlights: Effects on host population dynamics precede effects on adult bee health. Immune-related enzymes and learning performance are predictive of colony collapse. Varroosis strongly linked to changes in body composition of winter bees. Abstract: The parasitic mite Varroa destructor, in interaction with different viruses, is the main cause of honey bee colony mortality in most parts of the world. Here we studied how effects of individual-level parasitization are reflected by the bee colony as a whole. We measured disease progression in an apiary of 24 hives with differing degree of mite infestation, and investigated its relationship to 28 biometrical, physiological and biochemical indicators. In early summer, when the most heavily infested colonies already showed reduced growth, an elevated ratio of brood to bees, as well as a strong presence of phenoloxidase/prophenoloxidase in hive bees were found to be predictors of the time of colony collapse. One month later, the learning performance of worker bees as well as the activity of glucose oxidase measured from head extracts were significantly linked to the timing of colony collapse. Colonies at the brink of collapse were characterized by reduced weight of winter bees and a strong increase in their relative body water content. Our data confirm the importance of the immune system, known from studies of individually-infested bees, for the pathogenesis of varroosis at colony level. However, they also show that single-bee effects cannot always be extrapolated to the colony as a whole. This fact, together with the prominent role of colony-level factors like the ratio between brood and bees for disease progression, stress the importance of the superorganismal dimension of Varroa research.